AtDAT1 Is a Key Enzyme of D-Amino Acid Stimulated Ethylene Production in Arabidopsis thaliana - Suarez, Juan; Hener, Claudia; Lehnhardt, Vivien-Alisa; Hummel, Sabine; Stahl, Mark; Kolukisaoglu, Üner (Frontiers in Plant Science, 2019)
D-Enantiomers of proteinogenic amino acids (D-AAs) are found ubiquitously, but the knowledge about their metabolism and functions in plants is scarce. A long forgotten phenomenon in this regard is the D-AA-stimulated ethylene production in plants. As a starting point to investigate this effect, the Arabidopsis accession Landsberg erecta (Ler) got into focus as it was found defective in metabolizing D-AAs. Combining genetics and molecular biology of T-DNA insertion lines and natural variants together with biochemical and physiological approaches, we could identify AtDAT1 as a major D-AA transaminase in Arabidopsis. Atdat1 loss-of-function mutants and Arabidopsis accessions with defective AtDAT1 alleles were unable to produce the metabolites of D-Met, D-Ala, D-Glu, and L-Met. This result corroborates the biochemical characterization, which showed highest activity of AtDAT1 using D-Met as a substrate. Germination of seedlings in light and dark led to enhanced growth inhibition of atdat1 mutants on D-Met. Ethylene measurements revealed an increased D-AA stimulated ethylene production in these mutants. According to initial working models of this phenomenon, D-Met is preferentially malonylated instead of the ethylene precursor 1-aminocyclopropane-1-carboxylic acid (ACC). This decrease of ACC degradation should then lead to the increase of ethylene production. We could observe a reciprocal relation of malonylated methionine and ACC upon D-Met application and significantly more malonyl-methionine in atdat1 mutants. Unexpectedly, the malonyl-ACC levels did not differ between mutants and wild type. With AtDAT1, the first central enzyme of plant D-AA metabolism was characterized biochemically and physiologically. The specific effects of D-Met on ACC metabolism, ethylene production, and plant development of dat1 mutants unraveled the impact of AtDAT1 on these processes; however, they are not in full accordance to previous working models. Instead, our results imply the influence of additional factors or processes on D-AA-stimulated ethylene production, which await to be uncovered.